The effects of foraminotomy and intervertebral distraction on the volume of the lumbosacral intervertebral neurovascular foramen: An ex vivo study. (February 2020) - Smolders, L.A.; Knell, S.C.; Park, B.; Pozzi, A.; Meij, B.P.; Steffen, F.
Highlights: Surgical treatments for lumbosacral foraminal stenosis include foraminotomy and distraction-stabilization. Both foraminotomy and distraction-stabilization caused an enlargement of the lumbosacral intervertebral neurovascular foramen. Foraminotomy and distraction-stabilization caused an enlargement of the lumbosacral intervertebral neurovascular foramen. Only foraminotomy enlarged the subcompartment of the intervertebral neurovascular foramen where the L7 nerve root was located. Foraminotomy was more effective for treating nerve root compression caused by foraminal stenosis. Abstract: Degenerative lumbosacral stenosis in dogs frequently involves L7-S1 foraminal stenosis and L7 nerve root compression. Surgical techniques to decompress the L7 nerve root include foraminotomy and intervertebral distraction. The objective of this study was to compare the effect of foraminotomy and intervertebral distraction on the total, cranial, and caudal compartmental volumes of the L7-S1 intervertebral neurovascular foramen (NF). CT images were obtained from eight canine lumbosacral (L5-CD1) specimens in the following sequential conditions: native spine (1), after dorsal laminectomy and partial discectomy of L7-S1 (2), after L7-S1 foraminotomy (3), after distraction with an interbody cage between L7 and S1 (4), after cage distraction stabilized with pedicle screw-rod fixation in neutral (5) and flexed position (6). The volume of the complete NF and its cranial and caudal subcompartments were calculated using the CT images and statistically compared between conditions. P < 0.05 was considered statistically significant. The volume of the complete NF was significantly increased after foraminotomy (mean ± standard deviation (146.8 ± 26.5%, P < 0.01) and after distraction (Condition 4, 121.0 ± 19.1%; Condition 5, 116.6 ± 29.3 %; Condition 6, 119.0 ± 21.8 %; P = 0.01) with no difference between the distraction conditions. Foraminotomy induced a significantly larger increase in total NF volume compared to distraction. Foraminotomy, but not distraction, induced a significant increase in volume of the cranial subcompartment (158.2 ± 33.2 %; P < 0.01). Foraminotomy is more effective in increasing the foraminal volume and especially the cranial subcompartment, which is where the L7 nerve root traverses the NF. Hence, foraminotomy may be more effective in decompressing the L7 nerve root.